A Flexible Approach to Terminological Definitions: Representing Thematic Variation. (23rd September 2021) - San Martín, Antonio
Abstract: To formulate definitions that meet user needs, terminologists and specialised lexicographers must know how to effectively select information. However, most definition writing guidelines are based on the specification of necessary and sufficient characteristics, which has serious drawbacks because it downplays the role of context (understood as any factor affecting how a term is interpreted) in specialised meaning construction. This paper focuses on thematic variation, an important type of contextual variation, and its representation in terminological definitions. To this end, this paper presents a corpus-based approach to writing definitions that takes into account thematic variation in the selection of information.